2018
DOI: 10.1099/jgv.0.001064
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia-mediated protection of Drosophila melanogaster against systemic infection with its natural viral pathogen Drosophila C virus does not involve changes in levels of highly abundant miRNAs

Abstract: The presence of Wolbachia confers virus protection to insects. The molecular mechanism underlying Wolbachia-mediated protection in this tripartite host-endosymbiont-virus interaction is not yet fully understood. In the bipartite association between Drosophila melanogaster and Drosophila C virus (DCV), changes in the expression of microRNAs (miRNAs) influence the outcome of viral pathogenesis. Here we examined whether changes in miRNA expression are similarly involved in the Drosophila-Wolbachia-DCV association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The observed Wolbachia infection densities in the W8- w and W3- w cell lines are lower than previously reported for Drosophila , mosquito and sand fly host cells [35, 43, 44]. While higher Wolbachia infection densities have been reported to result in pathogen blocking and cytoplasmic incompatibility [41, 45, 46], other studies have suggested that low level infections can also result in cytoplasmic incompatibility (CI) and possibly pathogen blocking [47, 48]. Few studies have examined for Wolbachia infections in native Culicoides spp.…”
Section: Discussionmentioning
confidence: 90%
“…The observed Wolbachia infection densities in the W8- w and W3- w cell lines are lower than previously reported for Drosophila , mosquito and sand fly host cells [35, 43, 44]. While higher Wolbachia infection densities have been reported to result in pathogen blocking and cytoplasmic incompatibility [41, 45, 46], other studies have suggested that low level infections can also result in cytoplasmic incompatibility (CI) and possibly pathogen blocking [47, 48]. Few studies have examined for Wolbachia infections in native Culicoides spp.…”
Section: Discussionmentioning
confidence: 90%
“…We chose this approach because single primers sometimes fail to amplify their corresponding gene fragments in some strains (Simões et al ., 2011). As a positive control, we used extracted DNA of Drosophila melanogaster with a confirmed Wolbachia infection by w Mel strain (Monsanto‐Hearne and Johnson, 2018) for all PCRs. As part of a separate study, the amplicons generated by this study, including 16S, gatB, coxA and fbpA from 75 Wolbachia positive samples, were sent for Illumina pooled amplicon sequencing with 10–30 K coverage (Sanaei et al ., 2021a).…”
Section: Methodsmentioning
confidence: 99%
“…Wolbachia wMel-infected and uninfected Drosophila and mosquito cell lines (86) (87) or in live flies (88). In Ae.…”
Section: Previous Studies Have Not Found Significant Changes In the A...mentioning
confidence: 99%